2011
DOI: 10.1103/physreva.83.012502
|View full text |Cite
|
Sign up to set email alerts
|

High-precision frequency measurement of the 423-nm Ca i line

Abstract: We have performed an accurate frequency calibration of the 4s 2 1 S 0 → 4s4p 1 P 1 principal resonance line of the neutral calcium atom at 423 nm. Doppler-free cw excitation on a Ca atomic beam was performed by utilizing a Sagnac geometry in the alignment of the excitation beams. From frequency calibrations against a frequency comb, stabilized to a global positioning system (GPS) disciplined Rb standard, the transition frequency is determined at 709 078 373.01(35) MHz for the main 40 Ca isotope. Slightly lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Comparing our measured value of the 40 Ca 4s 21 S 0 → 4s4p 1 P°1 transition frequency to the value of 709 078 373.01(35) MHz from [30] shows good agreement, with our value 0.82 MHz higher. Our measurement cannot be considered definitive because the laboratory magnetic fields are not canceled.…”
Section: B Rb D1 Transitionsupporting
confidence: 87%
“…Comparing our measured value of the 40 Ca 4s 21 S 0 → 4s4p 1 P°1 transition frequency to the value of 709 078 373.01(35) MHz from [30] shows good agreement, with our value 0.82 MHz higher. Our measurement cannot be considered definitive because the laboratory magnetic fields are not canceled.…”
Section: B Rb D1 Transitionsupporting
confidence: 87%
“…The light shift is expected to be smaller than 0.3 MHz for all the measured transitions. This is estimated from the calculation for the shift due to neighboring transitions and from the measurements by other groups [4,5]. We have also experimentally confirmed that the light shift is negligibly small by measuring the resonance frequencies for different probe laser powers for the saturated absorption spectroscopy.…”
Section: Frequency Ratios Of Atomic Linesmentioning
confidence: 57%
“…40 Ca has the abundance of 96.9 % and the nuclear spin of 0. The absolute frequency of this transition is 709 078 373.01(35) MHz [4]. The excitation spectrum is observed by using the cold atomic beam (Fig.…”
Section: Frequency Ratios Of Atomic Linesmentioning
confidence: 98%
See 1 more Smart Citation
“…The frequency range is calibrated by the Ca atom isotope. The 423 nm transition frequency of 40 Ca and 44 Ca isotope is apart from 773.8 MHz [27]. …”
Section: Hanle Detection In Ca Atomic Beam Optical Frequency Standardmentioning
confidence: 99%